Gênero digital homepage em educação online: uma análise sociorretórica bidimensional - Campos, Karlene do Socorro da Rocha (2014)
This research is inserted in the fields of Linguistics and Distance Education, specifically of Online Education. It comprises the study of digital genre homepage on subjects of the graduation course Mathematics Teaching Education - Distance Mode offered by the Pontifical Catholic University of São Paulo (PUC-SP). We are based mainly on sociorhetorical conception of textual genre, in which genre is conceived as a pragmatic entity. In relation to this entity, the notions of purpose, context and action are interlinked. From this perspective, to produce a genre, users aim to achieve a certain purpose, and the success of the action that the genre conveys depends on the language choices appropriate to the communicative situation. Our hypothesis is that knowledge of the sociorhetorical organization of homepage genre helps the instructional designer in the development of educational activities that promote a positive interaction between participants of online distance learning courses and pedagogical contents, and consequently promote their involvement in the teaching and learning process. In order to test it, we examined this organization in homepages of courses offered in the 2nd half of 2012, considering the twodimensional analysis of genre model (ASKEHAVE; NIELSEN, 2004), that is founded on the sociorhetorical analysis proposed by Swales (1990), and that consider in the reading and navigating modes of digital genres, communicative purposes; functional units (rhetorical movements and links); and rhetorical strategies employed to achieve the communicative purpose. Primarily, we are based on studies of genre as social action (MILLER, 2009, 2009a [1984], 2009b [1992]; BAZERMAN, 2006 [1997]; 2009a [2004], 2009b [1994]; SWALES, 1990; BHATIA, 1993), as well as on studies of digital text genre (MARCUSCHI, 2010 [2004]; ASKEHAVE; NIELSEN, 2004) and hypertext (LEMKE, 2002; FINNEMANN, 1999). This thesis is a case study based on observation and description of a phenomenon in a specific context (MARTINS, 2008 [2006]; YIN, 1984; 2005 [2003]; TRIVIÑOS, 1987). The results obtained show that the knowledge of sociorhetorical organization of homepage genre provides an organization of pedagogical contents more oriented to interests and needs of users. Consequently, this knowledge contributes to the student engagement with the educational process